Contextual Teaching-Learning Method to Improve Student Engagement among College Students in Cognitive Psychology Course - Hazhira Qudsyi; Hariz Enggar Wijaya; Nur Widiasmara; Fani Eka Nurtjahjo (International Conferences on Educational, Social Sciences and Technology)
This study focus on how contextual teaching-learning (CTL), as one of learning method, can improve student engagement. Participants of this study were 156 college students in Yogyakarta, Indonesia. The study was conducted with an experimental approach. Measurement of student engagement was done by using School Engagement Scale. This scale was adapted into Indonesia version, and it has Cronbach’s Alpha coefficient 0.859 with 15 items. Result of data analysis showed that there was a significant difference on student engagement among college students (p=0.042), but student engagement scores in posttest was smaller than scores in pretest (N Negative Ranks = 83, Mean rank = 78.20; N Positive Rank = 64, Mean rank = 68.55; Ties = 9). Additional analysis was also discussed in this study.From this result, we can conclude that CTL not effective to improve student engagement among college students. Results and limitations of this study are discussed further in this paper.